2003
DOI: 10.1109/tmtt.2003.809186
|View full text |Cite
|
Sign up to set email alerts
|

Calibrated measurement of optoelectronic frequency response

Abstract: We describe the most straightforward method for accurately measuring the frequency response of optoelectronic devices. The method uses a calibrated optical reference receiver, a modulated optical source, and a calibrated electrical vector network analyzer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 90 publications
(37 citation statements)
references
References 24 publications
0
37
0
Order By: Relevance
“…As shown in Fig. 1b, the scattering matrix of the intrinsic laser can be expressed in terms of the light power at the output port, the incident-wave a and reflected-wave b at the input port [5].…”
Section: Extended Subtraction Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Fig. 1b, the scattering matrix of the intrinsic laser can be expressed in terms of the light power at the output port, the incident-wave a and reflected-wave b at the input port [5].…”
Section: Extended Subtraction Methodsmentioning
confidence: 99%
“…where Z r is usually set to be 50 Ω [5,6]. Therefore, the transfer function of the intrinsic laser can be expressed as…”
Section: Extended Subtraction Methodsmentioning
confidence: 99%
“…It has also been shown that one way of overcoming perturbation sensitivity (or 'interferometric noise') is to insert a sufficiently long length of fibre between the source of the reflections so that the multiple reflections are uncorrelated and do not add coherently [36]. However, it is still necessary to locate the position of the reflections (and their reflection coefficients) to have a completely characterized system [37].…”
Section: (Ii) Polarizationmentioning
confidence: 99%
“…(iv) Optical Cavity Effects Hale and Williams [37] point out that if both the optical source and photoreceiver in the transmission test set (Figure 10.13) have non-zero optical reflection coefficients, a Fabry-Perot resonator will be formed if an optical fibre is inserted between them. This situation is analogous to that considered in Figure 10.9.…”
Section: (Ii) Polarizationmentioning
confidence: 99%
See 1 more Smart Citation